PENGEMBANGAN MEDIA PEMBELAJARAN SMART BOX BERBASIS KEARIFAN LOKAL PADA MATA PELAJARAN IPAS KELAS V SD/MI - Dewi, Mona; M.Daud, Ridhwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the limited use of innovative learning media in the Natural and Social Sciences (IPAS) subject, resulting in students being less actively engaged and experiencing difficulties in understanding cultural diversity materials. This study aimed to develop a Smart Box learning media based on local wisdom for Grade V elementary school IPAS learning and to determine its validity and practicality. The study employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of six validators, namely two media experts, two material experts, and two language experts, as well as one Grade V teacher and 23 Grade V students who participated in the practicality test. Data were collected using validation and practicality questionnaires and analyzed quantitatively using descriptive statistics with a Likert scale. The results showed that the Smart Box learning media based on local wisdom obtained validation scores of 98% from media experts, 67% from material experts, and 92% from language experts, with an overall average of 85%, indicating that the media was highly valid. The practicality test results showed scores of 77% from students and 96% from the teacher, with an overall average of 86%, indicating that the media was highly practical. Therefore, the local wisdom-based Smart Box learning media was considered highly valid and highly practical for use in Grade V elementary school IPAS learning and has the potential to support more contextual and engaging learning experiences.